The prediction model for advertising campaigns in IPTV networks based on the possibilities of displaying geographically targeted messages - Chmielewska Aleksandra Maria; Grabowski Marcin Tomasz (Studia Ekonomiczne i Regionalne)
This paper presents a novel predictive model for advertising campaigns in IPTV networks that uses the advanced geolocation-based display of advertising messages. Thanks to advanced data analysis and modern geolocation technologies, the proposed model enables the more precise planning and optimisation of advertising campaigns. Advertisers can thus better understand the preferences and behaviours of audiences in different geographical regions. This allows the creation of more tailored and engaging content of programmes and advertisements, leading to higher levels of viewer engagement in the content presented and increasing the effectiveness of campaigns.